Lifestyle and complementary therapies in multiple sclerosis guidelines: Systematic review. (17th January 2022) - Weld‐Blundell, Isabelle V.; Grech, Lisa; Learmonth, Yvonne C.; Marck, Claudia H.
Abstract : Management of multiple sclerosis (MS) may comprise clinical interventions and self‐management strategies, including complementary therapies and modifiable lifestyle factors such as exercise and smoking cessation. Lifestyle modifications and complementary therapies with proven safety and efficacy are essential as part of best‐practice MS management, especially when faced with limited access to healthcare services. However, it is unclear to what extent MS clinical practice guidelines and consensus statements address these strategies. A systematic review was conducted, wherein MEDLINE, EMBASE, PsycINFO, CINAHL, Scopus, Web of Science, guideline databases and developer sites were searched for guidelines and consensus statements that addressed lifestyle modifications and complementary therapies of interest. Two researchers independently screened articles, extracted data and assessed guideline quality using the Appraisal of Guidelines for Research and Evaluation version II. Thirty‐one guidelines and consensus statements were included. Quality was high for 'clarity of presentation' (77%) and 'scope and purpose' (73%), moderate for 'stakeholder development' (56%), 'rigour of development' (48%) and 'editorial independence' (47%), and low for 'applicability' (29%). Two guidelines, related to physical activity and exercise, mindfulness, smoking cessation, and vitamin D and polyunsaturated fatty acid supplementation, scored high in all domains. These guidelines were two of only four guidelines intended for use by people with MS. High‐quality guidelines and consensus statements to guide lifestyle modifications and complementary therapies in MS management are limited. Our findings indicate the need for more guidelines intended for use by people with MS, and a further focus on implementation resources.